(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The built environment significantly contributes to global energy consumption, greenhouse gas emissions, and water usage, necessitating innovative sustainable architectural approaches in civil engineering. This study provides a comprehensive analysis of sustainable design strategies, advanced building materials, and their environmental performance to support the transition toward low-impact construction practices. By systematically reviewing recent literature and conducting simulation-based case studies, the research evaluates the effectiveness of passive design principles, low-carbon materials, and integrated building systems across diverse climatic contexts. Life cycle assessment (LCA) and life cycle cost analysis (LCCA) are employed to quantify the environmental and economic impacts of various architectural interventions over a building’s lifespan. Key findings highlight the critical role of passive design elements—such as optimized building orientation, high-performance envelopes, and natural ventilation—in reducing operational energy demand. Among materials, mass timber and geopolymer concrete emerge as promising low-embodied carbon alternatives with favourable durability profiles. Trade-offs between embodied carbon and operational savings are identified, underscoring the importance of holistic assessment frameworks. Additionally, daylighting strategies not only improve occupant comfort but also reduce reliance on artificial lighting, further cutting energy use. The study’s insights offer actionable recommendations for policymakers, practitioners, and rating bodies (e.g., ECBC, GRIHA, LEED) to refine codes and promote sustainable construction. Emphasizing integrated design and material choices is essential to achieve net-zero goals and advance resilient, eco-friendly civil infrastructure.